The missing future: Colombian youth - Rodrigo Parra Sandoval (CEPAL Review, 1986)
The exhaustion of the modernization rood el, the acute crisis affecting the family and the shortcomings of political and educational institutions place Colombian young people in a state of isolation characterized, in the author’s view, by few opportunities of political participation, a future of unemployment or underemployment, poor-quality education which inspires no enthusiasm and guarantees neither employment or social mobility, and a society without a clear model of a future with a place in it for young people. Young people are also faced with a chaos of values generated not only by the very rapid succession of three social situations (rural society, modern society and model-less society) but also by the emergence of forms of organization connected with that succession, such as the black economy, the economic organization of drug-traffiking or dependence on drugs, corruption in the world of finance and administration, and the consumerist visions offered by the mass communication media.